2019
DOI: 10.1021/acs.jpcc.9b05537
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon Nanotubes/Nanofibrillar Cellulose/Nafion Composite-Modified Tetrahedral Amorphous Carbon Electrodes for Selective Dopamine Detection

Abstract: Vasuki Durairaj) 2 ABSTRACT: We introduce a composite membrane comprising of multi-walled carbon nanotubes (MWCNTs) dispersed in a matrix of sulfated nanofibrillar cellulose (SNFC) and Nafion. The high negative charge densities of the SNFC and Nafion ionomers enhance the cationic selectivity of the composite. The composite is characterized by scanning electron (SEM) and transmission electron (TEM) microscopies as well as Fourier transform infrared (FTIR) and Raman spectroscopies. Tetrahedral amorphous carbon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The introduction of PEI on the hydrophobic ta-C surface is thus considered to be successful in anchoring the drop-cast nanocellulose/MWCNT membranes, without the need for any additional polymeric binders in the composite, as previously used. 23 Electrochemical measurements in blank electrolyte solutions further verify that the introduction of PEI does not passivate the ta-C substrate (Figure S7). Structural stabilities of the drop-cast electrode membranes were also investigated in deionized water.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…The introduction of PEI on the hydrophobic ta-C surface is thus considered to be successful in anchoring the drop-cast nanocellulose/MWCNT membranes, without the need for any additional polymeric binders in the composite, as previously used. 23 Electrochemical measurements in blank electrolyte solutions further verify that the introduction of PEI does not passivate the ta-C substrate (Figure S7). Structural stabilities of the drop-cast electrode membranes were also investigated in deionized water.…”
mentioning
confidence: 81%
“…16−22 We have previously demonstrated that the presence of a high density of negatively charged sulfate functional groups on the nanocellulose can significantly improve the selectivity of multiwalled carbon nanotubes (MWCNTs) in the composite electrode, toward the cationic dopamine molecule. 23 The use of such nanocellulose/ nanocarbon composites in electrochemical applications has become increasingly popular in the recent years. 24−30 However, this field is still very much at its early stages, and there is a lack of systematic studies regarding the effects of the nanocellulosic material properties, upon the electrochemical performance of such composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, active materials were employed in modifying supporting to achieve an enhanced and distinguishable chemical signal response. The use of active materials, including carbon balls [29][30], graphene [31][32][33][34], and carbon nanotubes [35] indicate that carbon materials facilitate the electrical analysis signal response of DA and UA [36].…”
Section: Introductionmentioning
confidence: 99%